Peranan E-Government dalam Meningkatkan Kualitas Pelayanan Publik di Mal Pelayanan Publik Kota Malang - Hari Purnomo; Suljatmiko; Ihsan (Jurnal Administrasi Publik dan Pemerintahan, 2025)
This study aims to analyze the role of E-Government in improving the quality of public services in the Malang City Public Service Mall (MPP). The problem of slow, inefficient, and non-transparent public services is the basis for the importance of digital transformation through the implementation of E-Government. This study uses a qualitative method with a descriptive approach and a case study design. Data was collected through in-depth interviews with MPP managers, front office officers, and service user communities, complemented by observation and documentation studies. The results of the study show that the implementation of electronic queue systems, self-service kiosks, East Java Smart Service (JSS) applications, and NIK-DTKS data integration is able to accelerate the public service process with an average time efficiency of 50-60%. In addition, the level of public satisfaction with speed, ease of access, and service quality tends to be high. However, the challenges faced are the digital literacy gap of the community and the limited capacity of service human resources. This study recommends strengthening digital literacy, increasing human resource capacity, and strengthening infrastructure and cross-sector collaboration to support the sustainability of digital transformation of public services.